2004
DOI: 10.1128/iai.72.1.576-583.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Induction of Neospora caninum Bradyzoites in Vero Cells Reveals Differential Antigen Expression, Localization, and Host-Cell Recognition of Tachyzoites and Bradyzoites

Abstract: We report on an optimized method for the in vitro culture of tissue cyst-forming Neospora caninum bradyzoites in Vero cells and the separation of viable parasites from host cells. Treatment of tachyzoite-infected Vero cell cultures with 17 M sodium nitroprusside for 8 days severely scaled down parasite proliferation, led to reduced expression of tachyzoite surface antigens, and induced the expression of the bradyzoite marker NcBAG1 and the cyst wall antigen recognized by the monoclonal antibody MAbCC2. Transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 59 publications
6
71
0
1
Order By: Relevance
“…However, major antigenic differences do exist between the different stages of N. caninum i.e. the tachyzoite, the bradyzoite and the oocyst [48,49]. These three stages can be observed in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…However, major antigenic differences do exist between the different stages of N. caninum i.e. the tachyzoite, the bradyzoite and the oocyst [48,49]. These three stages can be observed in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…BAG1, a classical bradyzoite-specific marker (McAllister et al 1996;Vonlaufen et al 2002Vonlaufen et al , 2004, was used to monitor the conversion efficiency. For this purpose, parasites were purified from SNP-treated cells and the expression levels of BAG1 and BAG1 mRNA were compared with those of tachyzoites by immunofluorescence (IF) and quantitative RT-PCR (qRT-PCR), respectively ( Fig.…”
Section: Cell and Parasite Culturesmentioning
confidence: 99%
“…The relevant role of GRA proteins in the closely related T. gondii is well known: GRA proteins constitute a highly immunogenic group which are excreted/secreted by dense granules to the parasitophorous vacuole during parasite intracellular development (Cesbron-Delauw 1994). In particular, GRA7 is a highly immunogenic, dense granule protein in both T. gondii and N. caninum (Lally et al 1997, Fischer et al 1998, Vonlaufen et al 2004, which has been effectively employed as a diagnostic tool (Aguado-Martínez et al 2008). Moreover, although GRA proteins appear to be related to intracellular parasite development, previous studies Characterisation of Neospora caninum NcGRA7 and NcSAG4 proteins 305 revealed that NcGRA7 might be involved in the initial host cell invasion process of N. caninum (Augustine et al 1999, Cho et al 2005.…”
Section: Introductionmentioning
confidence: 99%